Numerical and experimental analysis of the dynamic response of a blocky portal frame with elastic joints (Proceedings of Faculty of Civil Engineering, 2025)
This paper investigates the dynamic response of a block-based portal frame with elastic joints. A nonlinear numerical model based on discrete kinematics was developed and implemented in Python using the Newmark method. Experimental tests were conducted to validate the model. Results confirm its suitability for analyzing block systems and form a basis for future extension to nonlinear joint behavior.
Keywords: dynamic excitation; portal frame; numerical model; elastic joints; block systems